Mangrove Vegetation Analysis in Forest Area of Batu Bara Regency - ginting, eva; Anita Zaitunah; Orang Kaya Hasnanda Syahputra (Journal of Sylva Indonesiana, 2025)
The forest area in Batu Bara Regency is managed by Unit X KPHL Batu Bara, which has a coastal area with coastal forest characteristics and is dominated by mangrove ecosystems. Currently, the condition of land cover in the forest area in Batu Bara Regency has undergone many changes in terms of function and designation, so an analysis is needed to determine the condition of the mangrove ecosystem. Spatial analysis was carried out to ensure the area with mangrove vegetation land cover in the Unit X Batu Bara management area, which will then be the basis for determining the location of the mangrove vegetation analysis. Based on the results of spatial analysis of changes in land cover, land cover in Unit X KPHL Batu Bara is dominated by dry land agriculture and ponds. Meanwhile, land covered with secondary mangrove forest criteria has increased in area from previously ± 297.79 Ha (8.11%) to ± 535.89 Ha (14.59%). Based on vegetation analysis, the results of the study indicate that the condition of the mangrove ecosystem in KPH Unit X KPHL Batu Bara is currently in a condition of sparse density for tree classification, moderate density for sapling classification, and dense for seedling classification with moderate species diversity.